Development of Herbarium Book as Biology Instructional Media in Plant Morphology Subject for Biology Education Undergraduate Students, University of Pasir Pangaraian - Dahlia Dahlia (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2020)
The development of instructional especially media of a herbarium book is an innovation that aims to assist students in searching directly the object of leaf morphology studies. This development research starts from the needs analysis stage which is used to gather information, planning in media making, media design, media making, after that product validation by a team of media experts and material experts, then testing individual products, small groups and large groups. The subject of this product testing were students of the Biology Education Study Program at Pasir Pengaraian University. The results of the validation by the material experts showed that the quality of learning media using the herbarium book on leaf morphology material was included in the